The effects of increasing rates of AIDS-related illness and death on rural families in Zombia district, Malawi: A longitudinal study - Peters, Pauline E.; Kambewa, Daimon; Walker, Peter (International Food Policy Research Institute, 2008)
The primary purpose of the research conducted from January to December 2006 was to investigate the ways in which the AIDS epidemic was playing out in a Zomba District sample of households that had been studied since 1986. The single most important characteristic of this research is that we have information on the same households for twenty years, a span of time for a longitudinal study that we believe to be unique in current research in Malawi.